A revised classification of the cleft lip and palate. Issue 1 (March 2013) - Khan, Mansoor; Ullah, Hidayat; Naz, Shazia; Iqbal, Tariq; Ullah, Tahmeed; Tahir, Muhammad; Ullah, Obaid
Background: Submucous cleft palate is characterized by muscular diastasis of the velum in the presence of intact mucosa with variable combinations of bifid uvula and hard palatal defect. Submucous cleft palate is indicated as a separate entity in most previous classifications but it has never been properly classified on an anatomical basis. Objectives: To revise the Smith-modified Kernahan 'Y' classification of cleft lip and palate deformities, and to describe the different anatomical subtypes of submucous cleft palate. Methods: The present study was conducted in Hayatabad Medical Complex, Abasin Hospital and Aman Hospital Peshawar, Pakistan, from November 2010 to December 2011. All patients who presented to the outpatient departments with cleft lip and palate, with the exception of previously operated cases, were included. All cases were described according to the Smith-modified Kernahan 'Y' classification and the authors' revised Smith-modified Kernahan 'Y' classification. All of the data were organized and analyzed using SPSS version 17 (IBM Corporation, USA). Results: A total of 163 cases of cleft lip and palate deformities were studied, of which 59.5% were male and 40.5% were female. Smith modification of the Kernahan 'Y' classification completely described the cleft deformities in 93.9% of patients. However, while the Kernahan 'Y' classification represented the submucous cleft palate, it did not describe its different anatomical subtypes in 6.13% of patients. The revised Smith-modified Kernahan 'Y' classification completely described the cleft deformities of the entire study population, including the different submucous cleft palate patients. Discussion: The Smith alphanumeric modification of the Kernahan 'Y' classification of cleft lip and palate came into existence after a long search and a series of modifications over the past century. This classification system describes the cleft region, site of the cleft, degree of the cleft, rare and asymmetrical clefts, and are computer database friendly. However, this classification did not describe the different anatomical subtypes of submucous cleft palate that have variable relationships with velopharyngeal insufficiency. Conclusion: The revised Smith-modified Kernahan 'Y' classification described in the present study can describe all types of cleft lip and palate deformities in addition to the different types of submucous cleft palate deformities.